p Penerapan Sistem Pembelajaran Berbasis Peta Pikir - Luh Putu Ida Harini (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
The development of online learning systems is very rapid in the last ten years, various educational institutions have begun to use online learning systems to support the teaching and learning process. Along with this, students have become very fluent in using online learning systems, so this system can be an excellent choice for the learning process in the future. However, it will be very good when the learning system improves its capabilities, especially in helping teachers monitor the learning process carried out by students. In this study, a student function model was applied which is expected to be able to provide information to teachers about the character of their students in using the online learning system. This paper will discuss the assessment of the system designed, from a small-scale test of 5 teachers and 15 students, it was found that their opinion on the satisfaction of using the system reached 87%.